Status of the rare palm Bentinckia condapanna Berry in two habitats of Goodrical Reserve Forests; Western Ghats of India - Abhilash, ES; Sathian, Brijesh (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
Bentinckia condapanna shows more IVI values and there by dominance and ecological stress in both the sites, that is, in sparsely distributed habitats as well as in dominated habitats (Site-II). Major associations /co dominance to Bentinckia condapanna in site -I were the evergreen species like Macaranga peltata, Elaeocarpus tuberculatus, Lannea coromandelica, Schefflera venulosa etc. and for site-II was the secondary species Chionanthus ramiflorus. Higher IVI values for Bentinckia condapanna in both the sites proves the capacity of this species to establish in mono-dominant and co- dominant communities. DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9503 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1: 6-9